Long-acting somatostatin analogue treatments in autosomal dominant polycystic kidney disease and polycystic liver disease: a systematic review and meta-analysis. Issue 1 (9th January 2020) - Griffiths, Joshua; Mills, Mark T; Ong, Albert CM
Abstract : Objectives: A number of randomised control trials (RCTs) investigating the effects of long-acting somatostatin analogues in autosomal dominant polycystic kidney disease (ADPKD) and polycystic liver disease (PLD) have been recently reported. We sought to evaluate all available RCTs investigating the efficacy of somatostatin analogues treatment in ADPKD and PLD. Data sources: Electronic databases; Pubmed, Clincaltrials.gov and Cochrane Central Register of Controlled Trials Eligibility criteria for selecting studies: RCTs and randomised cross-over trials comparing the effects of somatostatin analogue treatment with controls in patients with ADPKD or PLD. Data extraction and synthesis: Data extraction and bias assessments were performed by two independent reviewers between January and May 2019. Outcomes assessed included estimated glomerular filtration rate (eGFR), total kidney volume (TKV), total liver volume (TLV), progression to end stage renal failure (ESRF) and adverse effects. Data were pooled using a random-effects model and reported as relative risk or mean difference with 95% CIs. Results: Meta-analysis was performed of six RCTs or randomised cross-over trials and three secondary analyses. A total of 592 patients were included. Compared with controls, somatostatin analogue treatment significantly reduced TLV (mean difference −0.15 L, 95% CI −0.26 to −0.03, p=0.01). There was no significant effect on TKV (mean difference −0.19 L, 95% CI −0.50 to 0.12, p=0.23) or eGFR (mean difference 0.27 mL/min/1.73 m 2, 95% CI −2.03 to 2.57, p=0.82). There was no effect on progression to ESRF. Somatostatin analogues were associated with known adverse effects such as gastrointestinal symptoms. Conclusions: The available RCT data show improvement in TLV with somatostatin analogue treatment. There was no benefit to TKV or eGFR in patients with ADPKD, while being associated with various side effects. Further studies are needed to assess potential benefit in reducing cyst burden in patients with PLD.